2021
DOI: 10.1097/qmh.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Suicide Audit: An Enhanced Method to Assess System Gaps and Mobilize Leaders for Prevention

Abstract: Background and Objectives: In Quebec, Canada, several independent processes are in place to investigate cases of death by suicide. An enhanced multidisciplinary audit process was developed to analyze these cases more thoroughly, with the aim of generating recommendations for suicide prevention. A study was undertaken to evaluate the feasibility and implementability of this process. Methods: The life trajectories of 14 people who died by suicide in Montreal, Canada, in 2016 were reconstructed on the basis of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A second set of variables are contact with primary care physicians and specialist mental health care, and Emergency Departments (ED) visits, which are indicative of greater need for care, but not always receiving adequate care. Systematic audits have shown that half of suicide cases were in contact in the last year with the ED, 50% in contact with a general practitioner and 25% with a psychiatrist, and deficits have consistently been found in the 3 areas, i.e., coordination of specialist mental health and specialist addiction services at the ED; poor access to referral by general practitioners to specialist mental health or addiction consultation; poor access to mobile crisis resolution teams in support of outpatient services [ 10 ]. The increased risk of suicide among patients presenting for non-intentional trauma at the ED may be due to alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A second set of variables are contact with primary care physicians and specialist mental health care, and Emergency Departments (ED) visits, which are indicative of greater need for care, but not always receiving adequate care. Systematic audits have shown that half of suicide cases were in contact in the last year with the ED, 50% in contact with a general practitioner and 25% with a psychiatrist, and deficits have consistently been found in the 3 areas, i.e., coordination of specialist mental health and specialist addiction services at the ED; poor access to referral by general practitioners to specialist mental health or addiction consultation; poor access to mobile crisis resolution teams in support of outpatient services [ 10 ]. The increased risk of suicide among patients presenting for non-intentional trauma at the ED may be due to alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%
“…In the SHAP summary plot, the top variables, including age, specialist outpatient visits for physical disorders in the past 60 months, regional mental budget, regional dependence budget, psychiatric outpatient psychotherapy in the past 60 months, and quality of local area primary care for depression, provided the insight into the local area programs where the individual lives [ 12 , 72 ]. The association with other specialist physical health visits may seem to be counterintuitive, but it is related to the deficits in identifying suicide risk and consultation with physical mental health or addiction services, as evidenced by at least one case [ 10 ]. Similarly, while capturing the quality of psychiatric outpatient visits with potentially effective and relevant treatments like psychotherapy, the modeling indicated that the low number of psychotherapy visits with a psychiatrist in the past 60 months was associated with lower risk, but not the local area quality of primary care physician practices for depression where the individual was living associated with lower risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations